Ameloblastoma - Haryono, Dedy C.; Purnomo, Joko; Philo, Richard (International Surgery Journal, 2023)
Ameloblastoma is a noncancerous tumor that originates from epithelial tissue in the oral cavity. It is regarded as one of the most aggressive odontogenic tumors (OT) in several nations throughout the world. If left untreated, they can grow to be quite big, causing facial disfigurement and functional issues. The treatment of ameloblastoma depends on the size, location, and histological subtype of the tumor. Surgical resection is the mainstay of treatment, and various techniques have been developed to minimize morbidity and recurrence.